Case Report: Acute onset hemiparesis in a young man: do not miss Crohn’s disease - Iacobelli, Virginia; Tagliabue, Simone; Modello, Beatrice; Velardo, Daniele; Abati, Elena; Triulzi, Fabio; Comi, Giacomo Pietro; Corti, Stefania; Gagliardi, Delia; Parisi, Mosè (Frontiers in Immunology, 2025)
Crohn’s disease (CD) is a chronic inflammatory bowel disease that may include neurological complications, besides gastrointestinal manifestations. Although cerebrovascular complications are commonly reported, cerebral vasculitis remains an exceedingly rare occurrence and only a limited number of cases have been described. We present the case of a 35-year-old man with CD who presented with acute onset of right-sided hemiparesis, hemiataxia and paresthesias. Laboratory data showed an inflammatory profile. Contrast-enhanced brain magnetic resonance angiography (MRA) with vessel wall imaging well demonstrated focal areas of contrast enhancement in the perforating arteries and distal arterial branches of intracranial vessels, raising the suspicion of a vasculitic process. The patient was then started on high-dose steroid therapy with immediate improvement of the neurological condition. Follow-up brain MRA revealed a significant reduction of the focal contrast-enhancing alterations. If not accurately identified and promptly treated, vasculitic processes may lead to significant disabilities in young patients and should be considered in the differential etiologies of juvenile stroke since symptoms can improve with immunosuppressive treatment. This case highlights the broad spectrum of possible etiologies to be considered in a young patient presenting with an acute onset neurological syndrome and provides a stepwise approach to developing a comprehensive differential diagnosis.